Deteksi cemaran Staphylococcus aureus pada ayam krispy lokal di sekitar salah satu universitas kota Medan - Yayuk Putri Rahayu; D. Elysa Putri Mambang; Haris Munandar Nasution; Adelia Ramadani (Journal of Pharmaceutical and Sciences, 2023)
Chicken meat is more in demand by consumers because it is easy to process, can be accepted by all levels of society and has an economical price. Food poisoning can be caused by enterotoxin contamination caused by Staphyococcus aureus. Management of chicken meat that is not up to standard and unhygienic can affect human health. The purpose of this study was to identify the presence of pathogenic bacteria S. aureus in crispy fried chicken meat from roadside carts and local fast food at one of Medan city University and to analyze the contamination value of S. aureus bacteria whether it meets the Indonesian National Standard (SNI) < 1X102 CFU/ml. The research method is employed to detect the presence of S. aureus in samples using both Baird Parker Agar Base (BPA) and Egg Yolk media simultaneously. Quantification of S. aureus contamination is carried out through the application of the Total Plate Count (TPC) method. Findings from two samples of local fried chicken, namely samples A and B, indicate a positive result for the presence of S. aureus, with contamination levels exceeding the threshold of 1 x 102 CFU/ml. This leads to non-compliance with the established SNI standards. Conversely, in the case of local crispy fried chicken samples C and D, the results indicate a negative presence of the S. aureus pathogenic bacteria, with contamination levels not exceeding the threshold of 1 x 102 CFU/ml. Therefore, these results comply with the stipulated SNI standards.